Longitudinal evaluation of neuroinflammation and oxidative stress in a mouse model of Alzheimer disease using positron emission tomography - Luka Rejc; Vanessa Gómez-Vallejo; Ana Joya; Gemma Arsequell; Ander Egimendia; Pilar Castellnou; Xabier Ríos-Anglada; Unai Cossío; Zuriñe Baz; Leyre Iglesias; Estibaliz Capetillo-Zarate; Pedro Ramos-Cabrer; et al. (Alzheimer’s Research & Therapy, 2022)
Abstract Background Validation of new biomarkers of Alzheimer disease (AD) is crucial for the successful development and implementation of treatment strategies. Additional to traditional AT(N) biomarkers, neuroinflammation biomarkers, such as translocator protein (TSPO) and cystine/glutamine antiporter system (xc -), could be considered when assessing AD progression. Herein, we report the longitudinal investigation of [18F]DPA-714 and [18F]FSPG for their ability to detect TSPO and xc - biomarkers, respectively, in the 5xFAD mouse model for AD. Methods Expression of TSPO and xc - system was assessed longitudinally (2–12 months of age) on 5xFAD mice and their respective controls by positron emission tomography (PET) imaging using radioligands [18F]DPA-714 and [18F]FSPG. In parallel, in the same mice, amyloid-β plaque deposition was assessed with the amyloid PET radiotracer [18F]florbetaben. In vivo findings were correlated to ex vivo immunofluorescence staining of TSPO and xc - in microglia/macrophages and astrocytes on brain slices. Physiological changes of the brain tissue were assessed by magnetic resonance imaging (MRI) in 12-month-old mice. Results PET studies showed a significant increase in the uptake of [18F]DPA-714 and [18F]FSPG in the cortex, hippocampus, and thalamus in 5xFAD but not in WT mice over time. The results correlate with Aβ plaque deposition. Ex vivo staining confirmed higher TSPO overexpression in both, microglia/macrophages and astrocytes, and overexpression of xc - in non-glial cells of 5xFAD mice. Additionally, the results show that Aβ plaques were surrounded by microglia/macrophages overexpressing TSPO. MRI studies showed significant tissue shrinkage and microstructural alterations in 5xFAD mice compared to controls. Conclusions TSPO and xc - overexpression can be assessed by [18F]DPA-714 and [18F]FSPG, respectively, and correlate with the level of Aβ plaque deposition obtained with a PET amyloid tracer. These results position the two tracers as promising imaging tools for the evaluation of disease progression. Graphical abstract Longitudinal in vivo study in the 5xFAD mouse model shows that TSPO and oxidative stress assessment through [18F]DPA-714 and [18F]FSPG-PET imaging, respectively, could serve as a potential tool for the evaluation of Alzheimer disease progression.